Fetal Renal Echogenicity Associated with Maternal Focal Segmental Glomerulosclerosis: The Effect of Transplacental Transmission of Permeability Factor suPAR - Shuster, Shirley (J Clin Med, 2018)
We report a case of a pregnant woman with nephrotic syndrome due to biopsy-proven focal segmental glomerulosclerosis (FSGS) whose fetus developed echogenic kidneys and severe oligohydramnios by 27 weeks of gestation. Maternal treatment with prednisone resulted in normalization of the amniotic fluid indices and resolution of fetal renal echogenicity. The newborn was noted to have transient renal dysfunction and proteinuria, resolving by 6 weeks postpartum. The transplacental passage of permeability factors is postulated to have caused both the fetal and newborn renal presentation, with significantly elevated levels of soluble urokinase-type plasminogen activator receptor (suPAR) noted in the cord blood. This case documents the transplacental maternal-fetal transmission of suPAR, demonstrating the potential for maternal-fetal transmission of deleterious, disease-causing entities, and adds to the differential diagnosis of fetal echogenic kidneys. Further, this is the first documentation of a fetal response to maternal systemic therapy.